Teaching-Learning Mathematics in the Constructivist Classroom A Field Experience - K, Vijayan. (JOURNAL OF INDIAN EDUCATION, 2014)
Teaching mathematics to those students who do not have a strong base in mathematics is challenging. Same is the case for learning mathematics as far as the students are concerned. The present paper explains probable reasons for this issue supported with empirical evidences which are collected through multitude of sources during a three-month field visit at Central School for Tibetans, Bylakkupe, Karnataka. Past performance in mathematics of tenth standard students and the opinion of teacher concerned about student’s performance in mathematics were taken as a background for undertaking a small action research. The study combined both quantitative and qualitative research techniques for collecting and interpreting data. Triangulation methodology was incorporated for drawing appropriate conclusions. Findings reveal that poor performance in maths can be explained by correlates like students’ mathematical base, attitude towards mathematics, study habits and parental involvement.